Carceral alliance: vernacular professionalization and containment in Puerto Rican drug rehabilitation - Parker, Caroline Mary (Carceral communities in Latin America, 2021)
This chapter explores an alliance that is crystallizing in post-industrial Puerto Rico between drug offenders’ search for job opportunities and state projects of containment. It explores this alliance through the concept of “vernacular professionalization.” This refers to a dual strategy that is at once an entrepreneurial life project through which criminalized men seek to cultivate a labor market niche as “certified re-educated ex-addicts,” and also a governing strategy through which the commonwealth state seeks to lower the cost of containing and rehabilitating drug offenders. It argues that vernacular professionalization flourishes as a collective collusion only because of the utility these subjects pose to the carceral state, not because it opens a viable route to social mobility outside of this circumscribed carceral circuit.